National road cliff protection analysis in Malibau Anai after Anai River flood, West Sumatra - Istijono Bambang; Yuhendra Rahmad; Thariqjabbar Hape Muhammad; Mahdi; Dodi Arian; Al Giffari Muhammad; Hakam Abdul; Martanto Adji Bayu; Menghoung Seng (E3S Web of Conferences)
Scouring of the riverbed can lead to landslides and erosion of the river bank. Landslides on river cliffs are a type of slope failure caused by the swift flow of rivers which can be worse during flash floods events. In this discussion, cliff protection is analyzed at the location 0°29'36 “S 100°20'20” E on the Padang- Bukittinggi national road, which suffered significant damage due to the Anai River flood. With a road elevation of +373 m and a river bed elevation of +317 m, the 56 m high escarpment, which is only 3 m from the edge of the national road, is highly vulnerable to erosion and landslides. This study used field surveys for geotechnical measurements, and hydrological analysis to assess the stability of the cliff and the effectiveness of proposed protection measures, such as reducing river flow velocity, shifting the road, and improving drainage channels. The results show that although natural protection methods have shown positive results, they are insufficient and ineffective when facing of large flood pressures. Recommendations for improvement include the construction of ground-sills and flow diverters in the Anai River, road drainage, planting stronger vegetation, shifting the road body, and regular monitoring.